Exploring the prognostic implications of programmed death-ligand 1 expression in canine nodal lymphoma: Insights from surface membrane expression, transcript amount and plasmatic levels - Alessandra Ubiali; Luiza Cesar Conti; Raffaella De Maria; Paola Emanuela Maria Dall'Ara; Laura Marconato; Roberta Ferrari; Damiano Stefanello; Maria Amati; Luca Aresu; Fulvio Riondato; Valeria Martini (Research in Veterinary Science, 2026)

Slab window opening beneath southwestern North America and its relationship to regional magmatism: Insights from numerical modeling - Rodrigo Pérez-Luján; Vlad Constantin Manea; Luca Ferrari; Shoichi Yoshioka (Earth and Planetary Science Letters, 2026)

Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Dietary lipid utilisation under different thermal conditions in flathead grey mullet (Mugil cephalus) - Silvia Natale; Federico Moroni; Ricardo Domingo-Bretón; Jaume Pérez-Sánchez; Marco Berrettini; Maria Giulia Ferrari; Francesco Dondi; Danilo Concu; Dario Vallainc; Stefano Carboni; Tomaso Patarnello; Pier Paolo Gatta; et al. (Frontiers in Marine Science, 2026)
Water temperature and dietary lipid levels are key factors influencing fish growth and metabolic homeostasis in aquaculture. This study aimed to understand the interactive effects on growth performance, metabolic response, gut microbiota, and gut evacuation dynamics in flathead grey mullet ( Mugil cephalus ). A 100-day feeding trial was carried out to assess the effects of two dietary lipid levels (10%, L10; 15%, L15) at 22 °C (LT) and 28 °C (HT). Specific growth rate (% day -1 ) was higher ( p < 0.05) at HT (0.90 ± 0.01 for both diets) than at LT (0.70 and 0.62 for L10 and L15, respectively). Feed intake at L15 diet was lower at both temperatures ( p < 0.05) while FCR was reduced only by HT and not by lipid levels. Serum metabolic profiling indicated that higher temperatures accelerated energy turnover, as evidenced by elevated serum glucose and lactate at HT across both dietary groups ( p < 0.05). Accordingly, fish at HT in both dietary treatments exhibited lower total protein and cholesterol ( p < 0.05), suggesting a more efficient utilisation of protein reserves and lipid processing to meet increased metabolic demands. Gut evacuation dynamics were described here for the first time in this species by sampling multiple intestinal sections at different time points (1, 3, 5, 7, 9, and 12 hours post-prandial). The intestine was almost completely empty by approximately 8 h post-prandial, with the notable exception of fish fed the HL diet at LT, where a significant delay in evacuation (18 h) was observed. This delay may be attributed to the combined effects of higher dietary lipid levels and lower temperatures, which both prolong digestion and intestinal transit times. Gut microbiota composition was primarily shaped by temperature, with a shift toward a specialised profile dominated by Cetobacterium at HT in both dietary groups. Overall, the results highlight that the combination of a 15% lipid diet and 28 °C was associated with the most positive outcomes among the tested conditions, providing further insight into how dietary composition and temperature modulate digestive physiology in flathead grey mullet.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Dietary Paecilomyces variotii single-cell protein supports growth and intestinal health in gilthead sea bream - Serena Busti; Trond M Kortner; Elin Christine Valen; Elisa Benini; Alessio Bonaldo; Charilaos Xiros; Fabio Brambilla; Daniel Scicchitano; Giorgia Palladino; Marco Candela; Marco Berrettini; Francesco Dondi; et al. (Aquaculture, 2026)

Cascade testing as the missing link in cancer prevention among Lynch syndrome families - Lea Godino; Giulia Erini; Giovanni Innella; Sara Miccoli; Simona Ferrari; Pamela Magini; Luca Caramanna; Martina Preite; Veronica Simoni; Daniela Turchetti (Familial Cancer, 2026)

Prediction of hop cone ripening through Internet of Things (IoT) and Machine Learning (ML) technologies - Giulia Oddi; Martina Galaverni; Laura Belli; Margherita Rodolfi; Luca Davoli; Gianluigi Ferrari; Tommaso Ganino (Computers and Electronics in Agriculture, 2025)

Air pollution, nasal microbiota, and bronchiolitis: understanding their interplay through a multilevel approach - Marco Cafora; Marco Severgnini; Chiara Favero; Camilla Ceccarani; Mirjam Hoxha; Clarissa Consolandi; Tania Camboni; Eva Pinatel; Gregorio Milani; Anna Luganini; Valentina Bollati; Anna Pistocchi; et al. (Environmental Research, 2025)

Forest fires in Caatinga: Risk modeling and priority areas for prevention - Mariana de Aquino Aragão; Nilton Cesar Fiedler; Alexandre Rosa dos Santos; Tais Rizzo Moreira; Antonio Henrique Cordeiro Ramalho; Robert Gomes; Patrícia Carneiro Souto; Telma Machado de Oliveira Peluzio; Jéferson Luiz Ferrari; Danilo Simões; Leonardo Duarte Biazatti; Fernanda Moura Fonseca Lucas (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

A journey of discovery: a multi-stage diagnostic procedure identifies Curtobacterium flaccumfaciens pv. allii as a new potential threat to maize - Francesca Gaffuri; Irene Ferraris; Alessia Follador; Alessia Travaglino; Luca Angheben; Antonina Rita Limongi; Alessandro Passera; Beniamino Cavagna; Piero Attilio Bianco; Massimo Delledonne; Paola Casati (Crop Protection, 2025)

Continuous flood monitoring using on-demand SAR data acquired with different geometries: Methodology and test on COSMO-SkyMed images - Luca Pulvirenti; Giuseppe Squicciarino; Luca Cenci; Luca Ferraris; Maria Virelli; Laura Candela; Silvia Puca (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Effect of simulated prolonged heat wave on biometric performance and HSP70 synthesis in the striped venus clam Chamelea gallina - Antonina De Marco; Vito Antonio Baldassarro; Maura Cescatti; Marzia Moretti; Laura Calzà; Luciana Giardino; Francesco Dondi; Maria Giulia Ferrari; Pier Paolo Gatta; Luca Parma; Alessio Bonaldo (Aquaculture, 2025)

Mapping the surface properties of the Asal-Ghoubbet rift by massive inversion of the Hapke model on Pleiades multiangular images - D.T. Nguyen; S. Jacquemoud; A. Lucas; S. Douté; C. Ferrari; S. Coustance; S. Marcq; A. Meygret (Remote Sensing of Environment, 2025)

Impact of Water Saturation on the Anisotropic Elastic Moduli of a Gas Shale - Jinwoo Kim; Alessio Ferrari; Russell Ewy; Luca Duranti; Lyesse Laloui (Rock Mechanics and Rock Engineering, 2025)
How water saturation affects elastic properties is particularly important for analyses of gas shales in unconventional reservoirs, but experimental data in defined partially saturated conditions are rare. We show that the elastic moduli of a gas shale vary significantly with water saturation whereas the static anisotropy does not. A series of repeated hydrostatic compression were carried out on a gas shale specimen at various water saturation states to determine the elastic moduli ( $${E}_{\text{v}}$$ E v and $${E}_{\text{h}}$$ E h ) as a function of degree of saturation ( $${S}_{\text{r}}$$ S r ). The elastic moduli were calculated from the reversible stress–strain curves after repeating confining pressure cycles. We found that, while water saturation increases, the elastic moduli peak at intermediate degree of saturation and then decreases to the minimum value at quasi-saturation. This evolution of the elastic moduli with degree of saturation may be explained by unifying two water retention mechanisms, adsorption and capillarity, that have overall competing effects on the stiffness. It is believed that adsorption softens the gas shale by reducing the friction of the load-bearing clay matrix, while capillary menisci stiffen the gas shale by providing stabilizing forces. The Young’s modulus anisotropy ( $${E}_{\text{h}}/E_{\text{v}}$$ E h / E v ) did not show appreciable change with degree of saturation. Confining pressure seems to be a more important control on changes in the static anisotropy. Analyzing the volumetric behavior of gas shales in unconventional reservoirs should take into account the degree of saturation dependency. Extrapolating the experimental results to in-situ conditions must be done with great care.

Unlocking the Potential of Marine Sidestreams in the Blue Economy: Lessons Learned from the EcoeFISHent Project on Fish Collagen - Lorenzo Dondero; Giulia De Negri Atanasio; Francesca Tardanico; Erica Lertora; Raffaella Boggia; Vittorio Capra; Agnese Cometto; Mattia Costamagna; Fi.L.S.E; Mirvana Feletti; Fulvio Garibaldi; Federica Grasso; et al. (Marine Biotechnology, 2025)
This review provides a general overview of collagen structure, biosynthesis, and biological properties, with a particular focus on marine collagen sources, especially fisheries discards and by-catches. Additionally, well-documented applications of collagen are presented, with special emphasis not only on its final use but also on the processes enabling sustainable and safe recovery from materials that would otherwise go to waste. Particular attention is given to the extraction process, highlighting key aspects essential for the industrialization of fish sidestreams, such as hygiene standards, adherence to good manufacturing practices, and ensuring minimal environmental impact. In this context, the EcoeFISHent projects have provided valuable insights, aiming to create replicable, systemic, and sustainable territorial clusters based on a multi-circular economy and industrial symbiosis. The main goal of this project is to increase the monetary income of certain categories, such as fishery and aquaculture activities, through the valorization of underutilized biomass.

An IoT-based data analysis system: A case study on tomato cultivation under different irrigation regimes - Martina Galaverni; Giulia Oddi; Luca Preite; Laura Belli; Luca Davoli; Ilaria Marchioni; Margherita Rodolfi; Federico Solari; Deborah Beghè; Tommaso Ganino; Giuseppe Vignali; Gianluigi Ferrari (Computers and Electronics in Agriculture, 2025)

Oligocene magmato-tectonic events influential in the development of Pb-Zn, Ag, and Au mineralization at the Plomosas deposit, southwestern Sierra Madre Occidental, Mexico - Paula Montoya-Lopera; Gilles Levresse; Luca Ferrari; Honza Catchpole; Luis Coto; Felipe Mar; Andrés Cárdenas-Castro (International Geology Review, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Assessment of a geomorphological-based design for coastal protection: The case of a wave-cut platform on the Bogliasco coast (Liguria Region, NW Italy) - Luca Carpi; Luigi Mucerino; Marco Ferrari (Regional Studies in Marine Science, 2024)

Adaptive responses of skeletal muscle to calcaneal tendon partial injury in rats: insights into remodeling and plasticity - Victoria Assis; Rosângela Vieira de Andrade; Ivo Vieira de Sousa Neto; Fabrício Reichert Barin; Gracielle Vieira Ramos; Octávio Luiz Franco; Otavio Nobrega; Raquel Agnelli Mesquita-Ferrari; Tainá Caroline dos Santos Malavazzi; Thiago dos Santos Rosa; Hugo de Luca Corrêa; Bernando Petriz; et al. (Molecular Biology Reports, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Radiolarian dating of cherts from the Artofago Cave: Insights into prehistoric lithic tool production and resource exploitation in Southern Tuscany, Italy - Dario Ferrari; Marco Chiari; Enrico Pandeli; Luca Bachechi (Revue de Micropaléontologie, 2024)

From molecules to organisms: A multi-level approach shows negative effects of trace elements from sewage sludge used as soil improver on honeybees - Andrea Ferrari; Michela Sturini; Beatrice De Felice; Francesco Bonasoro; Chiara Francesca Trisoglio; Marco Parolini; Roberto Ambrosini; Luca Canova; Antonella Profumo; Federica Maraschi; Carlo Polidori; Alessandra Costanzo (Journal of Hazardous Materials, 2024)

Herbicide and nutrient monitoring in surface waters and groundwater of a paddy district in northern Italy - Alice Tediosi; Federico Ferrari; Diego Voccia; Olfa Gharsallah; Lucrezia Lamastra; Lucio Botteri; Riccardo Rossi; Tommaso Ferrari; Nicola Ballerini; Giulio Luca Cristian Gilardi; Arianna Facchi (Environmental Science and Pollution Research, 2024)

Thermal tolerance as a driver of reef fish community structure at the isolated tropical Mid-Atlantic Ridge Islands - Débora S. Ferrari; Lucas T. Nunes; Kirsty L. Jones; Carlos E.L. Ferreira; Sergio R. Floeter (Marine Environmental Research, 2024)

Preventive and therapeutic vascular photobiomodulation decreases the inflammatory markers and enhances the muscle repair process in an animal model - Tainá Caroline dos Santos Malavazzi; Lucas Andreo; Andreia Martinelli; Maria Fernanda Setúbal Destro Rodrigues; Anna Carolina Ratto Tempestini Horliana; Sandra Kalil Bussadori; Kristianne Porta Santos Fernandes; Fabio Daumas Nunes; Raquel Agnelli Mesquita-Ferrari (Journal of Photochemistry and Photobiology B: Biology, 2024)

Short-chain fatty acids modulate the IPEC-J2 cell response to pathogenic E. coli LPS-activated PBMC - Melania Andrani; Luca Ferrari; Paolo Borghetti; Valeria Cavalli; Elena De Angelis; Francesca Ravanetti; Eleonora Dall'Olio; Paolo Martelli; Roberta Saleri (Research in Veterinary Science, 2024)

Short-term exposure to fine particulate matter exposure impairs innate immune and inflammatory responses to a pathogen stimulus: A functional study in the zebrafish model - Marco Cafora; Sabrina Rovelli; Andrea Cattaneo; Anna Pistocchi; Luca Ferrari (Environmental Pollution, 2024)

Remaining Loyal to Our Soil: A Prospective Integrated Assessment of Soil Erosion on Global Food Security - Martina Sartori; Emanuele Ferrari; Robert M'Barek; George Philippidis; Kirsten Boysen-Urban; Pasquale Borrelli; Luca Montanarella; Panos Panagos (Ecological Economics, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Pyrolysis: a promising technology for agricultural waste conversion into value-added products - Valdecir Ferrari; Mateus Torres Nazari; Nathalia Favarin da Silva; Larissa Crestani; Lucas Manique Raymundo; Guilherme Luiz Dotto; Jeferson Steffanello Piccin; Luis Felipe Silva Oliveira; Andrea Moura Bernardes (Environment, Development and Sustainability, 2024)

Industrial by-products-derived binders for in-situ remediation of high Pb content pyrite ash: Synergistic use of ground granulated blast furnace slag and steel slag to achieve efficient Pb retention and CO2 mitigation - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Maurizio Pietro Bellotto; Giorgio Ferrari; Roberto Pellay; Graziano Rilievo; Fabio Vianello; Alessia Famengo; Gabriella Salviulo; Gilberto Artioli (Environmental Pollution, 2024)

Effects of amber LED on inflammatory and regulatory monocytes and lymphocytes - Kaline de Brito Sousa; Tainá Caroline dos Santos Malavazzi; Maria Fernanda Setúbal Destro Rodrigues; Tamiris Silva; Lucas Andreo; Alessandro Melo Deana; Fabio Daumas Nunes; Sandra Kalil Bussadori; Raquel Agnelli Mesquita-Ferrari; Kristianne Porta Santos Fernandes (Journal of Photochemistry and Photobiology B: Biology, 2024)

The Late Cretaceous batholithic massifs of Sierra La Laguna and Sierra La Trinidad, southern Baja California, Mexico: constraints on extensional structures from geology, geochronology, and thermobarometry - Rodrigo Gutiérrez-Navarro; Luca Ferrari; Teresa Orozco-Esquivel; Gabriela Hernández-Quevedo; Roberto Maldonado (International Geology Review, 2023)

Life cycle assessment of chemical synthesis of genistein and its glucosyl derivatives to be employed in the modulation of angiogenesis of hepatocellular cancer - Chiara Ruini; Luca Rigamonti; Aldo Zanni; Giulia Bertani; Gianluca Carnevale; Erika Ferrari; Paolo Neri; Anna Maria Ferrari; Roberto Rosa (Sustainable Chemistry and Pharmacy, 2023)

Osmolarity modulates the de-differentiation of horse articular chondrocytes during cell expansion in vitro: implications for tissue engineering in cartilage repair - Elena De Angelis; Amelia Barilli; Roberta Saleri; Bianca Maria Rotoli; Francesca Ravanetti; Francesca Ferrari; Luca Ferrari; Paolo Martelli; Valeria Dall’Asta; Paolo Borghetti (Veterinary Research Communications, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Shifts in immune responses of an invasive alien species: A test of the evolution of increased competitive ability hypothesis using American Eastern gray squirrels in Italy - Claudia Romeo; Joel Filipe; Lucas A. Wauters; Stefano Comazzi; Federica Riva; Nicola Ferrari (Science of The Total Environment, 2023)

40 Ar/ 39 Ar muscovite geochronology of Arperos Basin inversion in Southern Mexico: new insights into cretaceous shortening initiation in southernmost North America - Michelangelo Martini; Luca Ferrari; Amabel Ortega Rivera (International Geology Review, 2023)

Areas of endemism and sampling bias of Pentatomidae (Heteroptera) in the Americas - João Afonso Poester-Carvalho; Kim Ribeiro Barão; Lucas Garcia da Costa; Augusto Ferrari (Journal of Insect Conservation, 2023)

SARS-CoV-2 antibodies in inflammatory neurological conditions: a multicentre retrospective comparative study - Cecilia Zivelonghi; Alessandro Dinoto; Sarosh R. Irani; Andrew McKeon; Andrea Pilotto; Alessandro Padovani; Stefano Masciocchi; Eugenio Magni; Chiara R. Mancinelli; Ruggero Capra; Giorgia T. Maniscalco; Irene Volonghi; et al. (Immunologic Research, 2023)
It is well established that neurological and non-neurological autoimmune disorders can be triggered by viral infections. It remains unclear whether SARS-CoV-2 infection induces similar conditions and whether they show a distinctive phenotype. We retrospectively identified patients with acute inflammatory CNS conditions referred to our laboratory for antibody testing during the pandemic (March 1 to August 31, 2020). We screened SARS-COV-2 IgA/IgG in all sera by ELISA and confirmed the positivity with additional assays. Clinical and paraclinical data of SARS-COV-2-IgG seropositive patients were compared to those of seronegative cases matched for clinical phenotype, geographical zone, and timeframe. SARS-CoV-2-IgG positivity was detected in 16/339 (4%) sera, with paired CSF positivity in 3/16. 5 of these patients had atypical demyelinating disorders and 11 autoimmune encephalitis syndromes. 9/16 patients had a previous history of SARS-CoV-2 infection and 6 of them were symptomatic. In comparison with 32 consecutive seronegative controls, SARS-CoV-2-IgG-positive patients were older, frequently presented with encephalopathy, had lower rates of CSF pleocytosis and other neurological autoantibodies, and were less likely to receive immunotherapy. When SARS-CoV-2 seropositive versus seronegative cases with demyelinating disorders were compared no differences were seen. Whereas seropositive encephalitis patients less commonly showed increased CSF cells and protein, our data suggest that an antecedent symptomatic or asymptomatic SARS-CoV-2 infection can be detected in patients with autoimmune neurological conditions. These cases are rare, usually do not have specific neuroglial antibodies.

Stress Response in Toxic Diatoms: The Effects of Abiotic Factors on Growth and RNA Content in Pseudo-nitzschia calliantha and in Pseudo-nitzschia multistriata - Luca Ambrosino; Marco Miralto; Lucia Barra; Angela Sardo; Maria Luisa Chiusano; Radiana Cozza; Michele Ferrari; Silvestro Greco (Journal of Marine Science and Engineering, 2023)
Pennate diatoms belonging to the genus Pseudo-nitzschia are important components of phytoplankton assemblages in aquatic environments. Among them, the bloom-forming species Pseudo-nitzschia calliantha and Pseudo-nitzschia multistriata are known as domoic acid producers, and are thus considered harmful for aquatic organisms and for human health. For these reasons, monitoring the abundance of such species, as well as identifying the growth conditions enhancing or inhibiting their growth, could help to predict eventual risks for aquatic communities and for humans by direct or indirect exposure to these toxic algae. In this work, we assessed the effects of different parameters (irradiance, temperature, salinity, and nutrients) on six Pseudo-nitzschia species by evaluating their specific growth rates and total RNA content. Our results—corroborated by statistical analyses of regression and correlation plots of control samples and samples exposed to stressful conditions, showed, as expected, a general decrease in growth rates under suboptimal levels of temperature, irradiance, salinity, and nutrient supply (especially under silicon depletion), that was usually accomplished by a general increase in RNA content inside cells. We hypothesized that increments in RNA levels in cells exposed to unfavorable conditions could be due to a relatively fast activation of the mechanisms of stress response.

Mechanistic insights into Pb and sulfates retention in ordinary Portland cement and aluminous cement: Assessing the contributions from binders and solid waste - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Maurizio Pietro Bellotto; Giorgio Ferrari; Roberto Pellay; Graziano Rilievo; Fabio Vianello; Gabriella Salviulo; Qiusong Chen; Gilberto Artioli (Journal of Hazardous Materials, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Comparison between cavernous sinus and jugular vein as post mortem sampling sites for blood metabolic profiles in wild red deer (Cervus elaphus) - Stefano Comazzi; Sharon Guanziroli; Alessia Giordano; Nicoletta Formenti; Tiziana Trogu; Luca Corlatti; Camilla Luzzago; Nicola Ferrari (European Journal of Wildlife Research, 2023)
Collection from jugular vein (JV) or intrathoracic cavity is the traditional procedure for blood sampling dead wildlife, but it is often source of preanalytical biases. Cavernous sinus of dura mater (CS) is an alternative site for withdrawal that may help to solve these issues but it has been used only for serology, while no data are available for biochemistry. This work compares metabolic profiles from CS and JV blood in red deer Cervus elaphus , to evaluate the usability of CS for metabolic profiling. A total of 134 deer were sampled in the frame of a culling program within the Stelvio National Park (Central Italian Alps). Hemolysis was statistically lower in CS than JV with 88% vs 44% of samples suitable for biochemistry. Thirty-six couples of poorly hemolytic sera were used for biochemical analysis: total protein, albumin, urea, triglycerides, total cholesterol, non-esterified fatty acids (NEFA), betahydroxybutyrate (BOHB), calcium, and phosphorus. Statistical differences were found for protein, albumin, cholesterol, and calcium; agreement was found for urea, NEFA, BOHB, and phosphorus while for total protein, albumin, cholesterol, and calcium, CS showed lower concentrations with both constant and proportional biases. These results may be related to a higher impact of water dilution in CS. Although the lower protein concentration in CS cannot significantly influence the serological results, caution is required for potential false negative results when antibody levels are close to cut-off values. CS leads to a higher percentage of samples suitable for metabolic profiles but results should be compared with adequate reference intervals.

The leaching behaviors of lead, zinc, and sulfate in pyrite ash contaminated soil: mineralogical assessments and environmental implications - Yikai Liu; Simone Molinari; Maria Chiara Dalconi; Luca Valentini; Giulia Ricci; Claudio Carrer; Giorgio Ferrari; Gilberto Artioli (Journal of Environmental Chemical Engineering, 2023)

Specifications and validation of the ACMG/AMP criteria for clinical interpretation of sequence variants in collagen genes associated with joint hypermobility - Maria Pia Leone; Silvia Morlino; Grazia Nardella; Riccardo Pracella; Daniela Giachino; Luca Celli; Demetrio Baldo; Licia Turolla; Maria Piccione; Emanuela Salzano; Martina Busè; Patrizia Lastella; et al. (Human Genetics, 2023)

Analysis and comparison of wellhead protection areas delimitation methods applying a stochastic MODFLOW model as a reference - Lucas Medeiros Bofill; Alexandra Vieira Suhogusoff; Luiz Ferrari; Ari Roisenberg (Environmental Monitoring and Assessment, 2023)

Neogene–Quaternary tectonic, eustatic and climatic events shaped the evolution of a South American treefrog - Tatianne Piza Ferrari Abreu‐Jardim; Natácia Evangelista de Lima; Lucas Jardim; Natan Medeiros Maciel; Rafael Félix de Magalhães; Guarino Rinaldi Colli; Célio Fernando Baptista Haddad; Rosane Garcia Collevatti (Journal of Biogeography, 2023)
Aim Understanding how past geological and climatic events could have generated intraspecific genetic variation at different temporal and spatial scales in the Neotropics requires a model encompassing distinct ecoregions. Because Anura species have their evolutionary history affected by climate and environmental changing, it is a suitable model to investigate the signatures of Neotropical historical events in species populations. Here we used a treefrog species to test hypotheses associated with tectonic, eustatic and climatic events along with isolation‐by‐environment and isolation‐by‐distance spatial patterns in genetic diversity. Taxon Scinax squalirostris (Lutz, 1925), Anura: Hylidae. Location Atlantic Forest, Cerrado, Chaco, Uruguayan Savanna and Pampas ecoregions in South America. Methods We sequenced nuclear and mitochondrial data from 219 individuals of S. squalirostris sampled at 26 locations in South America. We performed statistical phylogeographic analyses and reconstruction of spatiotemporal dispersal dynamics. Ecological niche modelling was conducted to predict spatial changes in environmental suitability from the Last Glacial Maximum to the Holocene and present day. Results We recovered a significant phylogeographic break roughly dated back to the Miocene (~7.6 Ma), coinciding with the retraction of marine incursions in the Paraná basin. Most dispersal events occurred in cooler periods of the Pliocene–Pleistocene transition. The spatial pattern in genetic diversity was not correlated with geographical distance or environmental variables. Main Conclusions Scinax squalirostris had a quasi‐stable distribution through time. Neogene – Quaternary tectonic, eustatic and climatic events drove the demographic history and dispersal dynamics of species, with a phylogeographical break dated to the Miocene coinciding with retractions of marine incursions in the Paraná basin. Lineage dispersal spread from the southern Atlantic Forest and retrieved gene flow signals congruent with the cold periods of the Pliocene and Pleistocene.

Packaging contaminants in former food products: Using Fourier Transform Infrared Spectroscopy to identify the remnants and the associated risks - Sharon Mazzoleni; Stefano Magni; Marco Tretola; Alice Luciano; Luca Ferrari; Cristian Edoardo Maria Bernardi; Peng Lin; Matteo Ottoboni; Andrea Binelli; Luciano Pinotti (Journal of Hazardous Materials, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

New UTfit analysis of the unitarity triangle in the Cabibbo–Kobayashi–Maskawa scheme - Marcella Bona; Marco Ciuchini; Denis Derkach; Fabio Ferrari; Enrico Franco; Vittorio Lubicz; Guido Martinelli; Davide Morgante; Maurizio Pierini; Luca Silvestrini; Silvano Simula; Achille Stocchi; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Prolonged heat waves reduce the condition index and alter the molecular parameters in the pacific oyster Crassostrea gigas - Antonina De Marco; Vito Antonio Baldassarro; Laura Calzà; Luciana Giardino; Francesco Dondi; Maria Giulia Ferrari; Giorgia Bignami; Luca Parma; Alessio Bonaldo (Fish & Shellfish Immunology, 2023)

Peripheral neuropathies during the COVID-19 pandemic: is there a relation? - Milena Trentinaglia; Giuseppe Lippi; Gian Luca Salvagno; Marianna G. Rispoli; Maria Vittoria De Angelis; Francesca Castellani; Daniela Alberti; Giorgia T. Maniscalco; Francesca Rossi; Mara Turri; Patrizia Rossi; Elisabetta Del Zotto; et al. (Immunologic Research, 2022)

Extracellular Vesicles: Footprints of environmental exposures in the aging process? - Paola Monti; Giulia Solazzo; Luca Ferrari; Valentina Bollati (Current Environmental Health Reports, 2021)

Invading parasites: spillover of an alien nematode reduces survival in a native species - Claudia Romeo; Anna Pia Piscitelli; Francesca Santicchia; Adriano Martinoli; Nicola Ferrari; Lucas A. Wauters (Biological Invasions, 2021)
It is widely assumed that spillover of alien parasites to native host species severely impacts naïve populations, ultimately conferring a competitive advantage to invading hosts that introduced them. Despite such host-switching events occurring in biological invasions, studies demonstrating the impact of alien macroparasites on native animal hosts are surprisingly few. In Europe, native red squirrels ( Sciurus vulgaris) are replaced by introduced North American grey squirrels ( S. carolinensis ) mainly through resource competition, and, only in the United Kingdom and Ireland, by competition mediated by a viral disease. In Italy such disease is absent, but spillover of an introduced North American nematode ( Strongyloides robustus ) from grey to red squirrels is known to occur. Here, we used long-term (9 years) capture-mark-recapture and parasitological data of red squirrels in areas co-inhabited by grey squirrels in Northern Italy to investigate the impact of this alien helminth on naïve native squirrels’ body mass, local survival, and reproduction of females. We found no negative effect of the alien parasite on body mass or reproductive success, but intensity of infection by S. robustus reduced survival of both male and female squirrels. Significantly, survival of squirrels co-infected by their native nematode, Trypanoxyuris sciuri , was less affected by S. robustus , suggesting a protective effect of the native helminth against the new infection. Hence, we demonstrate that alien S. robustus spillover adds to the detrimental effects of resource competition and stress induced by grey squirrels, further reducing the fitness of the native species in the presence of the invasive competitor.

Recreational beach tennis reduces 24-h blood pressure in adults with hypertension: a randomized crossover trial - Leandro Carpes; Alexandre Jacobsen; Lucas Domingues; Nathalia Jung; Rodrigo Ferrari (European Journal of Applied Physiology, 2021)

Correction to: Rip current hazard assessment on a sandy beach in Liguria, NW Mediterranean - Luigi Mucerino; Luca Carpi; Chiara F. Schiafno; Enzo Pranzini; Eleonora Sessa; Marco Ferrari (Natural Hazards, 2021)

Rip current hazard assessment on a sandy beach in Liguria, NW Mediterranean - Luigi Mucerino; Luca Carpi; Chiara F. Schiaffino; Enzo Pranzini; Eleonora Sessa; Marco Ferrari (Natural Hazards, 2021)
Rip currents are one of the most significant environmental hazards for beachgoers and are of interest to coastal scientists. Several studies have been conducted to understand rip current dynamics, and several approaches for rip hazard assessment have been proposed. In general, the purpose is to provide knowledge and tools to support authorities and lifeguards in rip current risk prevention. This study proposes the application of an expeditious methodology to evaluate rip current hazard and risk, based on probability theory. The tested area was located along the Alassio beach, a renowned tourist destination located on the western Ligurian coast (NW Italy). A coastal video-monitoring system was used for rip currents individuation, whereas wave data were collected thanks to an oceanographic buoy managed by Regione Liguria. In detail, a yearly analysis was performed to identify the correspondence between rip currents and wave parameters data. The results showed that rip currents occur, in the study area, under moderate wave conditions ( $$0.5 \le H_s \le 1.34$$ 0.5 ≤ H s ≤ 1.34 m; $$4.7\le T_m \le 7.0$$ 4.7 ≤ T m ≤ 7.0 s; $$150^{° }\,\hbox {N} \le θ _m \le 227^{° }$$ 150 ∘ N ≤ θ m ≤ 227 ∘ N). Based on this analysis, an easy application of the probability theory was applied to evaluate the level of hazard. Moreover, considering the official tourist data, we also perform an expeditious rip currents risk evaluation. The results showed that the hazard level is considered high at annual time scale and moderate during the tourist season; the risk is related to seasonal presences. The study can propose a tool to support authorities and lifeguards in water safety planning and management.

A hindcast study of the Piedmont 1994 flood: the CIMA Research Foundation hydro-meteorological forecasting chain - Antonio Parodi; Martina Lagasio; Agostino N. Meroni; Flavio Pignone; Francesco Silvestro; Luca Ferraris (Bulletin of Atmospheric Science and Technology, 2020)
Between the 4 th and the 6 th of November 1994, Piedmont and the western part of Liguria (two regions in north-western Italy) were hit by heavy rainfalls that caused the flooding of the Po, the Tanaro rivers and several of their tributaries, causing 70 victims and the displacement of over 2000 people. At the time of the event, no early warning system was in place and the concept of hydro-meteorological forecasting chain was in its infancy, since it was still limited to a reduced number of research applications, strongly constrained by coarse-resolution modelling capabilities both on the meteorological and the hydrological sides. In this study, the skills of the high-resolution CIMA Research Foundation operational hydro-meteorological forecasting chain are tested in the Piedmont 1994 event. The chain includes a cloud-resolving numerical weather prediction (NWP) model, a stochastic rainfall downscaling model, and a continuous distributed hydrological model. This hydro-meteorological chain is tested in a set of operational configurations, meaning that forecast products are used to initialise and force the atmospheric model at the boundaries. The set consists of four experiments with different options of the microphysical scheme, which is known to be a critical parameterisation in this kind of phenomena. Results show that all the configurations produce an adequate and timely forecast (about 2 days ahead) with realistic rainfall fields and, consequently, very good peak flow discharge curves. The added value of the high resolution of the NWP model emerges, in particular, when looking at the location of the convective part of the event, which hit the Liguria region.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Trans-splicing of plastid rps12 transcripts, mediated by AtPPR4, is essential for embryo patterning in Arabidopsis thaliana - Luca Tadini; Roberto Ferrari; Marie-Kristin Lehniger; Chiara Mizzotti; Fabio Moratti; Francesca Resentini; Monica Colombo; Alex Costa; Simona Masiero; Paolo Pesaresi (Planta, 2018)

Cortical and subcortical connections of parietal and premotor nodes of the monkey hand mirror neuron network - Stefania Bruni; Marzio Gerbella; Luca Bonini; Elena Borra; Gino Coudé; Pier Francesco Ferrari; Leonardo Fogassi; Monica Maranesi; Francesca Rodà; Luciano Simone; Francesca Ugolotti Serventi; Stefano Rozzi (Brain Structure and Function, 2017)

Identification of an atypical microdeletion generating the RNF135-SUZ12 chimeric gene and causing a position effect in an NF1 patient with overgrowth - Luca Ferrari; Giulietta Scuvera; Arianna Tucci; Donatella Bianchessi; Francesco Rusconi; Francesca Menni; Elena Battaglioli; Donatella Milani; Paola Riva (Human Genetics, 2017)

Novel insight in the life cycle of Torymus sinensis, biocontrol agent of the chestnut gall wasp - Chiara Ferracini; Elena Gonella; Ester Ferrari; Matteo Alessandro Saladini; Luca Picciau; Federica Tota; Marianna Pontini; Alberto Alma (BioControl, 2015)

Petrogenesis and geodynamic significance of silicic volcanism in the western Trans-Mexican Volcanic Belt: role of gabbroic cumulates - Chiara Maria Petrone; Teresa Orozco-Esquivel; Luca Ferrari (Contributions to Mineralogy and Petrology, 2014)

Effect of suboptimal environment and host age on helminth community of black grouse (Tetrao tetrix) - Nicoletta Formenti; Roberto Viganò; Luca Rotelli; Nicola Ferrari; Maria Chiara Cerutti; Paolo Lanfranchi (European Journal of Wildlife Research, 2013)

Exploring the effects of seasonality and chemical pollution on the hepatopancreas transcriptome of the M anila clam - Massimo Milan; Serena Ferraresso; Claudio Ciofi; Guido Chelazzi; Claudio Carrer; Giorgio Ferrari; Lino Pavan; Tomaso Patarnello; Luca Bargelloni (Molecular Ecology, 2013)
The assessment of marine environmental health is a complex but fundamental task both for ecosystem conservation and food safety related to the human consumption of marine products. Manila clams inhabiting the V enice L agoon constitute an excellent case study for evaluating the effects of complex mixtures of industrial and urban effluents on aquatic organisms. Clams were collected in different seasons at four locations within the V enice L agoon. The sampling sites were characterized by a range of pollutant concentrations and included P orto M arghera, a highly polluted industrial area where clam harvesting for human consumption is strictly forbidden. Pooled soft tissues were subjected to mass spectroscopy analysis to measure the concentrations of PCDD s/ PCDF s/ PCB s‐ DL , PCB s, PBDE s, HCB and PAH s, and pooled digestive gland samples were used for gene expression profiling. While seasonal variation was found to be responsible for the largest proportion of transcriptional changes, significance analysis of microarrays quantitative correlation analysis identified 162 transcripts that were correlated with at least one class of chemicals measured in the samples from the four different sampling sites. Prediction Analysis of Microarrays ( PAM ) identified a minimal set of seven genes that correctly assigned samples collected in the restricted polluted area ( P orto M arghera), independent of the season in which they were collected. An integrated approach combining transcriptomics and chemical analyses of the M anila clam provided a global picture of how M anila clams respond to complex mixtures of xenobiotics and their interplay with other biotic and abiotic factors. We were also able to identify gene expression signatures for different classes of chemicals and a set of robust biomarkers of exposure to these chemicals.

Sequential solidification/stabilization and thermal process under vacuum for the treatment of mercury in sediments - Alessandro Careghini; Sara Dastoli; Giorgio Ferrari; Sabrina Saponaro; Luca Bonomo; Luciano De Propris; Massimo Gabellini (Journal of Soils and Sediments, 2010)

Quaternary adakite—Nb-enriched basalt association in the western Trans-Mexican Volcanic Belt: is there any slab melt evidence? - Chiara M. Petrone; Luca Ferrari (Contributions to Mineralogy and Petrology, 2008)

Influence of Stage Discharge Relationship on the Annual Maximum Discharge Statistics - Ulderica Parodi; Luca Ferraris (Natural Hazards, 2004)

Catechol(amine)s as probes of lactoperoxidase catalytic site structure: spectroscopic and modeling studies - R. P. Ferrari; Silvio Traversa; Luca De Gioia; Piercarlo Fantucci; Gianpaolo Suriano; Elena M. Ghibaudi (JBIC Journal of Biological Inorganic Chemistry, 1999)